Strategic Use of User Generated Content for Consumer Engagement in Online Retail - Kahfi, fahrul; Suyuthi, Nurmadhani Fitri (Celebes Scholar pg, 2024)
The present research explores the managerial implication of employing User-Generated Content (UGC) to boost the consumer interactions in the web retail industry. Following a quantitative research method, cross-sectional data were obtained from 1,200 consumers through an online survey that measures their encounter with UGC, perceived trust level, engagement, and sales. The study shows that UGC specifically in the form of reviews and photos have a positive impact on the key engagement metrics such as website dwell time, repeat visitation ratio, and conversion ratios which prove the fact that UGC plays an important role in the digital marketing strategy. However, the study also established that UGC is only effective if it is well managed based on content selection, responding to negative messages, and compliance with ethical issues including the respect of consumer privacy and product author’s copyright. The study also reveals that there are variations in consumers’ UGC engagement by demographics: more particular, young consumers are more actively involved than other consumers, which calls for specific actions. These findings enrich the knowledge about UGC in the context of digital consumer behaviour and offer practical suggestions for online retailers that want to employ UGC to develop trust and sales in a more saturated market. Further research needs to be conducted with respect to the future of UGC due to continuous technological advancements like artificial intelligence and augmented reality among others that are likely to continually change consumption activities.